2012
DOI: 10.1055/s-0032-1301412
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis for Venous Thromboembolism: A Great Global Divide between Expert Guidelines and Clinical Practice?

Abstract: Our understanding of development and prevention of venous thromboembolism (VTE) has improved dramatically since Virchow described the triad of stasis, hypercoagulability, and endothelial dysfunction during the mid-1800s. A full arsenal of effective pharmacological and mechanical methods can help prevent VTE and many professional organizations have provided extensive evidence-based statements for VTE prophylaxis. Disappointingly, however, VTE has remained the major preventable cause of hospital death. Adherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 68 publications
0
16
0
1
Order By: Relevance
“…[1] Later low-molecular-weight heparin followed by a vitamin K antagonist became the recommended therapeutic regimen. [2] Vitamin K antagonists have also been the drugs of choice in preventing thrombo embolic events in patients with atrial fibrillation. The major problem with warfarin has been unpredictable pharmacodynamic and pharmacokinetic properties, including food and drug interactions, with resultant marked fluctuation in anticoagulation control in a significant number of patients.…”
Section: Researchmentioning
confidence: 99%
“…[1] Later low-molecular-weight heparin followed by a vitamin K antagonist became the recommended therapeutic regimen. [2] Vitamin K antagonists have also been the drugs of choice in preventing thrombo embolic events in patients with atrial fibrillation. The major problem with warfarin has been unpredictable pharmacodynamic and pharmacokinetic properties, including food and drug interactions, with resultant marked fluctuation in anticoagulation control in a significant number of patients.…”
Section: Researchmentioning
confidence: 99%
“…Sve tri komponente Virihovljeve trijade su prisutne u trudnoći i puerperijumu: hiperkoaguabilnost, venska staza i povreda krvnog suda [11].…”
Section: Patofiziološki Mehanizmiunclassified
“…While the problems of inappropriate test requests are often highlighted, recent data demonstrate that physicians face increasing difficulties in selecting the correct laboratory analyses due to the ever-increasing number and complexity of tests, the inadequacy of medical school training, and-at least for hemostasis-the insufficient awareness, compliance with, or even comprehension of, current guidelines and recommendations. [26][27][28][29] Within hemostasis testing, it was reported that physicians surprisingly experienced problems even in selecting the right test(s) for follow-up of common test abnormalities, such as a prolonged activated partial thromboplastin time (APTT). 30 Major challenges will likely emerge from monitoring of alternative anticoagulants, inasmuch as no definitive tests have been validated so far for agents such as lepirudin, and novel oral anticoagulants such as rivaroxaban, dabigatran, apixaban, and others.…”
Section: Examination (Test) Requestmentioning
confidence: 99%